Analysis of acoustic attenuation in impact noise and compression resistance of mortars for screed with partial replacement of natural aggregate by PCR-PET - Brandão, Raul de Souza; Lima, José Augusto Pedro; Alexandre, Jonas (National Journal of City Management, 2024)
This study aims to analyze the effects of partial replacement of natural aggregate with Post-Consumer Recycled Polyethylene Terephthalate (PCR-PET) in screed mortars, emphasizing both acoustic performance and compressive strength. The research adopts a methodological approach that encompasses material characterization to performance evaluation in terms of strength and acoustic attenuation. The originality of the work lies in the comprehensive analysis of the physical and mechanical properties of mortars, focusing on the effectiveness of replacing natural aggregate with PCR-PET. The results indicate that as the proportion of PCR-PET in the mix increases, the apparent density decreases, directly impacting compressive strength. Additionally, there is an improvement in sound absorption in mortars with higher substitution of sand by PCR-PET, highlighting positive implications for the acoustic performance of these materials. Theoretical and methodological contributions include a deeper understanding of mortar properties, while social and environmental implications reside in promoting sustainable practices in construction, emphasizing the potential use of recycled materials.
Keywords: Acoustic attenuation; Impact noise; Compression resistance; Mortars for subfloor